1997
DOI: 10.3168/jds.s0022-0302(97)76157-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fat Source on Duodenal Flow of Trans-C18:1 Fatty Acids and Milk Fat Production in Dairy Cows

Abstract: The objective of the study was to determine the effects of dietary fat source on duodenal flow, apparent absorption, and milk fat incorporation of trans-C18:1 fatty acids. Four ruminally and duodenally cannulated multiparous Holsteins cows in mid to late lactation were fed a basal diet containing 36% corn silage, 24% alfalfa haylage, and 40% concentrate (dry matter basis). Diets contained 0% supplemental fat (control diet), 3.7% high oleic sunflower oil, 3.7% high linoleic sunflower oil, or 3.7% partially hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
4
10

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 18 publications
7
66
4
10
Order By: Relevance
“…Based on the equation of Wu et al (1991), flaxseed supplementation reduced ruminal BH of total unsaturated C 18 , which agrees with some researchers (Klusmeyer and Clark 1991;Wu et al 1991;Pantoja et al 1996) but not others (Tice et al 1994;Hussein et al 1996;Kalscheur et al 1997). Beam et al (2000) reported that increasing the amount of fat in the diet induces a decline in the rate of lipolysis, which is the limiting step in ruminal BH of FA (Jenkins 1993).…”
Section: Biohydrogenation Of Fasupporting
confidence: 83%
See 1 more Smart Citation
“…Based on the equation of Wu et al (1991), flaxseed supplementation reduced ruminal BH of total unsaturated C 18 , which agrees with some researchers (Klusmeyer and Clark 1991;Wu et al 1991;Pantoja et al 1996) but not others (Tice et al 1994;Hussein et al 1996;Kalscheur et al 1997). Beam et al (2000) reported that increasing the amount of fat in the diet induces a decline in the rate of lipolysis, which is the limiting step in ruminal BH of FA (Jenkins 1993).…”
Section: Biohydrogenation Of Fasupporting
confidence: 83%
“…Effects of fat supplementation on total tract digestibility of LCFA are inconsistent. Feeding supplemental fat to dairy cows increased (Klusmeyer and Clark 1991;Romo et al 2000), decreased (Tice et al 1994;Hussein et al 1996) or had no effect (Wu et al 1991;Kalscheur et al 1997) on apparent total tract digestibility of individual FA.…”
Section: Intakes and Flows Of Famentioning
confidence: 98%
“…Kalscheur et al (1997) have also observed that vegetable oil-supplemented diets that maintain a normal ruminal environment have minimal effect on milk fat synthesis. Our study used a moderate (1.2% on a dry matter basis) level of SO, which probably did not upset the ruminal environment, as indicated by the absence of any effect on NDF or ADF digestibility values in Experiment 1 (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, Kalscheur et al (1997) have observed an increase in trans-18 : 1 after feeding high-oleic sunflower oil, and attribute this effect to a sufficient amount of dietary linoleic acid available for biohydrogenation. The response of trans-18 : 1 content in milk to increasing levels of dietary linoleic acid has not been established.…”
Section: Trans-fatty Acidsmentioning
confidence: 98%
“…However, their concentration in milk fat does not always indicate a reduction in milk fat (Kalscheur et al 1997). Recent work, summarized by Griinari et al (1997), suggests that the production in the rumen of the trans-10-18 : 1 isomer and its transfer to milk lipid is specifically responsible for the reduction in milk fat.…”
Section: Trans-fatty Acidsmentioning
confidence: 99%